Effects of some antiseptics on rate of Antarctic krill autoproteolysis - M. Fik; S. Bartosewicz (Acta Ichthyologica et Piscatoria, 1981)
Intensity of autoproteolysis in Antarctic krill (Euphausia superba) in the presence of some antiseptics was studied. The rate of autoproteolysis was assessed from release of amino and non-protein nitrogen in 100 g raw protein.